AFFECTING ABILITY TO SOLVE MATH STORY QUESTIONS STUDENTS 4th GRADE ELEMENTARY SCHOOL - Giri Prawiyogi, Anggy; Safarandes Asmara, Andes; Fatimah , Siti; Silviana (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to determine the difference between the effects of the problem-based learning model and those who do not use the problem-based learning model on the ability to solve mathematical story questions in 4th grade students of SD Negeri Adiarsa Barat II in 2018/2019. This research is a quantitative research with quasi experimental research type. With the sample used in this study amounted to 30 students with a population of 60 students. Data collection techniques using the ability to solve mathematical questions story in the form of essay. In testing the validity of the test the ability to solve mathematical story questions from 10 items all declared valid. The reliability test results obtained r11 finished 0.843. Hypothesis testing results, with the t- sig test (2 tailed) obtained 0.037 <0.05 with a tcount of 2.140> t table 1.699 then Ho is rejected, then it means there is a difference in the final value of the ability to solve mathematical story questions between students who use the Problem Based Learning model with who do not use the Problem Based Learning model. The results of this research concluded that there was a difference in the influence of the Problem Based Learning model on the ability to solve mathematical story questions in 4th grade SD Negeri Adiarsa Barat II in the 2018/2019 academic year.